Early Experience with Modified Dose Nirmatrelvir/Ritonavir in Dialysis Patients with Coronavirus Disease 2019. Issue 4 (1st April 2023) - Hiremath, Swapnil; Blake, Peter G.; Yeung, Angie; McGuinty, Michaeline; Thomas, Doneal; Ip, Jane; Brown, Pierre Antoine; Pandes, Michael; Burke, Andrew; Sohail, Qazi Zain; To, Karen; Blackwell, Lindsay; et al.
Visual Abstract: Abstract : Background: Nirmatrelvir/ritonavir was approved for use in high-risk outpatients with coronavirus disease 2019 (COVID-19). However, patients with severe CKD were excluded from the phase 3 trial, and the drug is not recommended for those with GFR <30 ml/min per 1.73 m 2 . On the basis of available pharmacological data, we developed a modified low-dose regimen of nirmatrelvir/ritonavir 300/100 mg on day 1, followed by 150/100 mg daily from day 2 to 5. In this study, we report our experience with this modified dose regimen in dialysis patients in the Canadian province of Ontario. Methods: We included dialysis patients who developed COVID-19 and were treated with the modified dose nirmatrelvir/ritonavir regimen during a 60-day period between April 1 and May 31, 2022. Details of nirmatrelvir/ritonavir use and outcomes were captured manually, and demographic data were obtained from a provincial database. Data are presented with descriptive statistics. The principal outcomes we describe are 30-day hospitalization, 30-day mortality, and required medication changes with the modified dose regimen. Results: A total of 134 dialysis patients with COVID-19 received nirmatrelvir/ritonavir during the period of study. Fifty-six percent were men, and the mean age was 64 years. Most common symptoms were cough and/or sore throat (60%). Medication interactions were common with calcium channel blockers, statins being the most frequent. Most patients (128, 96%) were able to complete the course of nirmatrelvir/ritonavir, and none of the patients who received nirmatrelvir/ritonavir died of COVID-19 in the 30 days of follow-up. Conclusions: A modified dose of nirmatrelvir/ritonavir use was found to be safe and well tolerated, with no serious adverse events being observed in a small sample of maintenance dialysis patients.